Effect of Nano bentonite on Fire Retardant Properties of Medium density fiberboard (MDF) - Ghonche Rassam; H.Reza Taghiyari; Ali Keshtegar; Farhad Kool (Iranian Journal of Wood and Paper Industries, 2014)
In the present study, Fire – Retarding properties of nano-bentonite in medium density of fiberboard (MDF) was studied. 10% of urea-formaldehyde resin was used as the adhesive of the matrix. Nano Bentonite at 5 levels (0%, 5%, 10%, 15% and 20%) g/kg based of dry weight of fibers was used with the consumption of Urea-Formuldehyde (UF). Press pressure of 150 bar and temperature of 170during 4, 5, and 6 minutes were applied. Density was kept constant at 0.7 g/cm3 in all treatments. The measured properties consisted of mass reduction, inflammation time, fire-endurance, melting time and the burnt area. The results revealed that Nano-Bentonite had significant effect in approving fire retarding properties in medium density fiber board. The best properties at the level of 10% obtained and the same level recommended for industry use. The use of Nano-Bentonite more than 10% decreased the stickiness and the partly surface of fiberboards.